PROBLEMS AND PROSPECTS OF THE FORMATION OF THE PROFESSION “NORM-WRITER” IN RUSSIA - Vladislav V. Grib (Сравнительная политика, 2019)
A large number of experts, professionals and journalists state that at present our country experiences a crisis of legality, constant adjustment, as well as gaps and inconsistency of legislation. The main reason for the current unfavorable situation, we believe, is the lack of specially trained representatives of the legal profession, specially prepared for lawmaking, ready to offer a balanced approach to the development and adoption of more stable laws that could regulate dynamic social relations and at the same time not be subjected to constant modernization. Such a difficult and often criticized work in the field of lawmaking requires a qualitative review of the composition of participants in legislative bodies at the federal and regional levels, representatives of ministries and departments whose activities are related to rule-making. At the same time, knowledge of fundamentals of legal engineering, analysis of the reasons for the increase in the number of acts deemed unconstitutional, acts inconsistent with acts of greater legal force, a study in retrospect of the quality of law-making activities of foreign countries and immersion in other disciplines in preparing a specially trained layer of representatives of the legal profession can in the end favorably affect the constancy and sustainability of the Russian legislation system. The purpose of the study is to substantiate the need for introducing a norm-writer profession, developing and implementing professional and educational standards. Methodological basis: deduction, abstraction, dialectical analysis of the results of law-making, historical and comparative methods for assessing the quality of the current legislation of Russia and foreign countries, generalizing problems and proposing ways out of the crisis in lawmaking. Results: in order to implement the project of training specially trained people ‒ norm-writers, the idea of the need to develop professional and educational standards was supported, while at the same time there was criticism of the feasibility of introducing benefits, incentives and other preferences. Conclusions: the knowledge and observance of a strictly formalized approach to the creation of a draft regulatory act, as well as the professional registration of draft acts by norm-writers, can bring the system of Russian legislation to a new level.